2020
DOI: 10.1002/mds.28170
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID‐19 on Parkinson's Disease Clinical Features: A Community‐Based Case‐Control Study

Abstract: The impact of coronavirus disease 2019 (COVID-19) on clinical features of Parkinson's disease (PD) has been poorly characterized so far. Of 141 PD patients resident in Lombardy, we found 12 COVID-19 cases (8.5%), whose mean age and disease duration (65.5 and 6.3 years, respectively) were similar to controls. Changes in clinical features in the period January 2020 to April 2020 were compared with those of 36 PD controls matched for sex, age, and disease duration using the clinical impression of severity index f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
238
1
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(260 citation statements)
references
References 31 publications
8
238
1
13
Order By: Relevance
“…Clinical implications of SARS-CoV-2 infection on PD are largely speculative apart from two case series and case reports 45,46 . A community-based case control study in Italy of 12 PD COVID-19 cases suggested substantial worsening of motor and non-motor symptoms during mild to moderate COVID-19 illness, independent of age and disease duration 144 , in line with an original case report series by Antonini et al In another survey across the Lombardy region of Italy, 105 probable COVID-19 cases were identified and the authors concluded that the risk, morbidity, and mortality in patients with mild-to moderate PD with COVID-19 did not differ from the general population 145 . Several viewpoints and editorials have been published on the topic in addition to extensive coverage in social media and journal viewpoint papers [146][147][148][149][150][151] .…”
Section: The Clinical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Clinical implications of SARS-CoV-2 infection on PD are largely speculative apart from two case series and case reports 45,46 . A community-based case control study in Italy of 12 PD COVID-19 cases suggested substantial worsening of motor and non-motor symptoms during mild to moderate COVID-19 illness, independent of age and disease duration 144 , in line with an original case report series by Antonini et al In another survey across the Lombardy region of Italy, 105 probable COVID-19 cases were identified and the authors concluded that the risk, morbidity, and mortality in patients with mild-to moderate PD with COVID-19 did not differ from the general population 145 . Several viewpoints and editorials have been published on the topic in addition to extensive coverage in social media and journal viewpoint papers [146][147][148][149][150][151] .…”
Section: The Clinical Perspectivementioning
confidence: 99%
“…4. Worsening of specific symptoms, including motor symptoms as well as non-motor issues, such as pain, anxiety, sleep disturbances and fatigue, especially with reduced access to physical therapy and counseling 45,144 . 5.…”
Section: The Clinical Perspectivementioning
confidence: 99%
“…Altered pharmacokinetics of the dopaminergic treatment or infection-related systemic inflammatory response were postulated as probable mechanisms. 33 Stress-related worsening of neurological diseases, particularly Parkinson's disease, dementia, MS and epilepsy, is a well-established fact and needs to be considered while attending to these patients. 34…”
Section: Covid-19-the Impact On Underlying Neurological Illnessesmentioning
confidence: 99%
“…Coronavirus infections typically affect the respiratory or gastrointestinal tracts; however, coronavirus-related neurological disease is receiving increased attention as the COVID-19 (SARS-CoV-2) pandemic progresses. Neurological manifestations of COVID-19 infections in humans have become more widely recognized as a significant component of clinical disease (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16); however, coronavirus involvement of the nervous system is not unique to the SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%